The relationship between renal cell carcinoma pathological types and perirenal fat area - Xin Leng; Chenchao Zhou; Jiulong Wu; Hongfang Zheng; Jianliang Wang; Qiaoxing Li; Yuhua Huang; Jianhu Liu (BMC Cancer)
Abstract Introduction To explore whether there is a relationship between perirenal fat area (PFA) and the pathological types of renal cell carcinoma (RCC). Methods Two hundred ninety-seven cases of RCC patients were included in our study, which is a retrospective analysis. Based on pathological type, we divided the 297 RCC patients into two groups: the clear cell renal cell carcinoma (ccRCC) group (236 cases) and the non-clear cell renal cell carcinoma (non-ccRCC) group (61 cases). Computed tomography (CT) images at the renal vein level were used to measure PFA. A multivariate logistic regression model was employed to examine the connection between various pathological types of RCC and PFA. Results Significant differences were observed between ccRCC and non-ccRCC patients in PFA (P = 0.007), contralateral PFA (P = 0.011), weight (P = 0.002), BMI (P < 0.001), pathological stage 1 (P = 0.010), and pathological stage 2 (P = 0.002). To study the link between pathological subtypes and PFA, a multivariate logistic regression model was employed. Stratifying patients by tumor location in the kidney, the multivariate logistic regression analysis showed that when the tumor is located outside the polar lines of the kidney (OPLK), for every 1 cm2 increase in PFA, the probability of developing ccRCC increases by 5% [1.05 (1.01, 1.10) P = 0.0153]. Furthermore, after stratifying patients by tumor location and pathological stage, it was found that in T1 stage patients with tumors located OPLK, for every 1 cm2 increase in PFA, the probability of developing ccRCC increases by 6% [1.06 (1.01, 1.11) P = 0.0300]. Conclusion When the tumor is located OPLK in T1 stage patients, PFA is positively correlated with ccRCC. Perirenal adipose tissue may be a risk factor for ccRCC.